Burn Care Service Training as a Public Health Intervention - Rai, Shanker Man (Journal of Nepal Health Research Council, 2021)
Burn injury is more common with low economic strata requiring holistic approach and support from multiple stake holders including the government to deal with this disability. Burn injury care is the specialized surgical service to be provided by highly trained human resource which can involve multiple specialist services, special care in a specialized burn center, special transportation service and financial coverage.Keywords: burn injury; care; cost; training